Development of agency skills and creative thinking among students of a technical university: practical cases - Oksana F. Abramova (RUDN Journal of Informatization in Education)
Problem statement . At the moment, we are in a transitional period of the formation of a new educational process, which is much broader and much more extensive than the classical methods of obtaining vocational education, both in terms of skill set and time. This is important for all areas of study, but this article focuses on educational processes at a technical university, or rather, areas of study related to information technology. Modern software development is usually carried out in teams. Emotional intelligence and the ability to put yourself in the place of your colleagues, as well as potential users of the software product, come to the fore. Stress tolerance and teamwork skills are also important qualities, which include the skills to independently solve non-standard tasks, the ability to take responsibility for solving a problem or for not completing a task, and the ability to follow the rules. The purpose of the study is to develop methods to improve the effectiveness of training a technical specialist, taking into account the challenges of the modern labor market. Methodology . The practical cases proposed in the article were tested in various training courses taught by the author on the basis of the Volga Polytechnic Institute. More than 70 students studying in the fields of Computer Science and Computer Engineering and Software Engineering took part in the testing. Results . Based on the analysis of the results of application of educational cases, detailed descriptions of tasks and recommendations for their application in the educational process were formulated. Conclusion . The application of the described practical cases allowed students to develop the ability to decompose tasks, distribute them within the team and consciously delegate execution depending on the set of knowledge and skills of an individual team member, as well as the ability to offer nonstandard solutions to tasks and adequately analyze existing options. Students studying using the above-mentioned cases participate much more calmly and effectively both in external educational activities, such as design and educational intensive courses, competitions and acceleration programs, and are more motivated and involved in the stages of implementation and protection of their own projects within the framework of disciplinary and end-to-end course projects, as well as final qualification work.